2017
DOI: 10.1007/s11064-017-2360-3
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like Effect of Bacopaside I in Mice Exposed to Chronic Unpredictable Mild Stress by Modulating the Hypothalamic–Pituitary–Adrenal Axis Function and Activating BDNF Signaling Pathway

Abstract: Preliminary studies conducted in our laboratory have confirmed that Bacopaside I (BS-I), a saponin compound isolated from Bacopa monnieri, displayed antidepressant-like activity in the mouse behavioral despair model. The present investigation aimed to verify the antidepressant-like action of BS-I using a mouse model of behavioral deficits induced by chronic unpredictable mild stress (CUMS) and further probe its underlying mechanism of action. Mice were exposed to CUMS for a period of 5 consecutive weeks to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 45 publications
0
18
0
2
Order By: Relevance
“…Depression is a chronic heterogeneous mental disease associated with high prevalence, recurrence, and mortality, with serious implications for human physical and mental health 1‐4 . The World Health Organization has predicted that by 2020 it will become the second leading cause of disability worldwide and by 2030 major depressive disorders (MDDs) will represent the main cost in healthcare spending 5,6 . Although progress has been made in the research and treatment of depression in recent years, the exact pathogenesis of this disease is still not clear, and experimental results from animal models are not in good agreement with those of clinical trials 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a chronic heterogeneous mental disease associated with high prevalence, recurrence, and mortality, with serious implications for human physical and mental health 1‐4 . The World Health Organization has predicted that by 2020 it will become the second leading cause of disability worldwide and by 2030 major depressive disorders (MDDs) will represent the main cost in healthcare spending 5,6 . Although progress has been made in the research and treatment of depression in recent years, the exact pathogenesis of this disease is still not clear, and experimental results from animal models are not in good agreement with those of clinical trials 7 .…”
Section: Introductionmentioning
confidence: 99%
“… 19 Moreover, depression-like effects in rats induced by chronic stress or glucocorticoid administration have been reported to be related to reduced hippocampal BDNF levels. 20 , 21 Furthermore, some antidepressants are reported to achieve their efficacy by increasing hippocampal BDNF expression. 22 , 23 Although the underlying mechanisms remain unknown, it has been reported that BDNF appears to be a direct target of Wnt signaling.…”
Section: Introductionmentioning
confidence: 99%
“…The antidepressantlike the action of bacon aside I (BS I) was investigated using a mouse model of behavioral deficits induced by chronic unpredictable mild stress (CUMS) for 5 weeks to induce depression. The oral administration of BS ameliorated CUMSinduced depression-like behaviors in mice reversed the increased level of plasma corticosterone and decreased mRNA and protein expressions of glucocorticoid receptor induced by CUMS exposure, indicating that hypothalamic-pituitary-adrenal (HPA) axis hyperactivity of CUMSexposed mice was restored by BS-I treatment 36 .…”
Section: Anti-depressant and Anti-anxiety Activitymentioning
confidence: 94%